A Study on Housing Affordability in Kolkata Urban Agglomeration (KUA), Based on Infrastructure Driven Housing Price Distribution and Household Income-Expenditure Pattern - Ankhi, Banerjee; Joy, Sen (International Journal of Property Sciences (E-ISSN: 2229-8568), 2013)
The paper attempts to assess variations in basic and composite housing affordability across Kolkata Urban Agglomeration (KUA) with respect to housing price distribution, patterns of household income and expenditure, and variations in transportation cost. Composite housing affordability represents total cost of living in a house within a particular location, and is indicative of the impact of off-site infrastructure on housing price as well as household expenditure; whereas basic housing affordability projects the link between house price and household income ignoring locational characteristics. In this paper, housing affordability assessment has been carried out using Price-to-income ratio, Median Multiple method and Residual Income approach, for surveyed households residing in group housing projects for low-to-middle income groups, across KUA. The study on housing price distribution together with variations in household income and expenditure of surveyed households reveal significant differences between non-inclusive or basic housing affordability and composite housing affordability across KUA. The housing market within KUA is found to range from mild un-affordability to severe un-affordability, necessitating immediate government intervention in both ownership and rental housing development of smaller unit sizes, affordable to the low-to-middle income group population.